Trade policy versus trade facilitation: An application using good old OLS - Laura Márquez-Ramos; Inmaculada Martínez-Zarzoso; Celestino Suárez-Burguet (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
Trade policy barriers are only one element of overall trade costs. Among these, and due to the decrease in the influence of tariff barriers on trade over time, institutional barriers might increase in relative importance and become a key obstacle to the movements of goods across countries. This paper quantifies and compares the impact that a number of trade facilitation and trade policy barriers have on bilateral trade flows. A theoretically justified gravity model of trade is estimated by using the methodology proposed in Baier and Bergstrand (Bonus vetus OLS: A simple method for approximating international trade-cost effects using the gravity equation, 2009) for a cross-section of countries in the year 2000. Results indicate that institutional trade barriers have a greater impact on trade flows than tariff barriers. According to these findings, trade policy negotiation efforts should focus on facilitating trade processes and should be at the forefront of multilateral negotiations.
Keywords: F14; 330; tariff barriers; trade facilitation; sectoral trade; Außenhandelsbeschränkung; Zollpräferenz; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Nichttarifäre Handelshemmnisse; Welt